1990
DOI: 10.2500/105065890782020962
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Carotid Artery as it Relates to Endonasal Sphenoethmoidectomy

Abstract: A better understanding of the pathogenesis of chronic sinus disease has led to an increased performance of endonasal sphenoethmoid surgery. Approaching the sphenoid sinus via this route mandates that the surgeon be aware of the anomalies which may be encountered in this region, if injury to the related neurovascular structures is to be avoided. This study was therefore undertaken to evaluate a critical anatomic variation, the incidence of bony dehiscence over the carotid artery. Following cadaver sphenoethmoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 11 publications
1
24
0
2
Order By: Relevance
“…Although we have found a constant asymmetry between both cavities of the sphenoid sinus, the identification of an asymmetric intersphenoid septum is very important especially when it shows a considerable deviation, as its advance marks the line of the internal carotid artery, which may protrude into the posterior ethmoid cells (Kennedy et al 1990). …”
Section: Other Variantsmentioning
confidence: 69%
“…Although we have found a constant asymmetry between both cavities of the sphenoid sinus, the identification of an asymmetric intersphenoid septum is very important especially when it shows a considerable deviation, as its advance marks the line of the internal carotid artery, which may protrude into the posterior ethmoid cells (Kennedy et al 1990). …”
Section: Other Variantsmentioning
confidence: 69%
“…Inspite of the complex anatomy and important surgical relationships of the sphenoid sinus, a very few recent reports focus on it (Lang, 1989;Kennedy et al, 1990;Sethi et al,.1995 ;Elwany et al, 1983 and. No such study has been reported from the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…8 Others have suggested a dehiscence rate as high as 22%. 9 Injury to the carotid can be from a laceration with immediate massive hemorrhage, pseudoaneurysm formation with delayed hemorrhage, or present with neurologic changes Box 10 Experience with management of this drastic although rare complication comes from the endoscopic skull base literature, where extended skull base approaches can have rates of ICA injury of around 5%. 11 First and foremost, it is critical to adequately and thoroughly review all imaging and specifically check for carotid dehiscence before performing surgery near the sphenoid.…”
Section: Internal Carotid Artery Injurymentioning
confidence: 99%